Solvent system selection in counter-current chromatography using conductor-like screening model for real solvents - Hopmann, Elisabeth; Arlt, Wolfgang; Minceva, Mirjana (Journal of Chromatography A, 2011)
The aim of this investigation was to minimize the experimental effort for solvent system selection in counter-current chromatography. The separation mechanism in counter-current chromatography is based exclusively on the partitioning of the solute between the two liquid phases. Therefore, a quantum chemical method combined with statistical thermodynamics (conductor-like screening model for real solvents, COSMO-RS) was used for the prediction of the partition coefficient. A comparison of the experimental and predicted data for five model solutes systems demonstrated the potential of the use of COSMO-RS as a screening tool for the solvent system selection. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Counter-current chromatography; Solvent system selection; Solvent system screening; COSMO-RS; Two-phase liquid system